Thiết kế bài thực hành đọc hiểu Ngữ văn lớp 10 - Châu Kim Vàng, Châu Kim Vàng; Trần Thị Nâu, Trần Thị Nâu (Tạp chí Giáo dục, 2024)
Designing the 10th grade Literature reading comprehension practice lesson aims to form independent reading competence in students to meet the requirements of the 2018 General Education Program in Literature. However, the program and the three current 10th grade Literature textbooks do not specify the content and how to organize reading comprehension teaching activities for 10th grade students. Teachers still face many difficulties in implementing this content. This article presents the reading comprehension practice and structure of the reading comprehension practice lesson in the 10th grade Literature textbook, the design of the reading comprehension practice lesson and the illustration design of the reading comprehension practice lesson on the text “Spirit Pillars of Heaven” in Literature textbook grade 10, Kite series. Designing reading comprehension practice lessons needs to highlight the characteristics of Literature, helping students form specific and general competences as well as necessary qualities in the learning process.